Critical appraisal of the International Study Group of Pancreatic Surgery (ISGPS) consensus definition of postoperative hemorrhage after pancreatoduodenectomy - Welsch, Thilo; Eisele, Hanna; Zschäbitz, Stefanie; Hinz, Ulf; Büchler, Markus W.; Wente, Moritz N. (Langenbeck's archives of surgery, 2011)
Postpancreatectomy hemorrhage (PPH) is one of the most serious complications after pancreatoduodenectomy (PD). This study analyzed and validated the International Study Group of Pancreatic Surgery (ISGPS) definition of PPH and aimed to identify risk factors for early (<24 h) and late PPH.